Social justice and community college education - Reece, Bryan (New York, NY : Routledge, 2021)
"This book explores the central role community colleges play in American social justice. The U.S. has long-standing social and cultural structures that perpetuate inequality along race, ethnicity and income lines. The primary role of American community colleges is to disrupt these structures on behalf of the students we serve. In this sense, community colleges are called to play a subversive role in contemporary society, but it is a good kind of subversion. Social Justice Education makes four very important contributions to this conversation. First, the book helps us quantify and understand the size and dimension of the equity gaps in higher education by tracking 10 specific student groups from historically underserved communities. Second, the book summarizes best practices research and literature with regard to pedagogy, services, programs, and leadership in community colleges, presenting practical strategies for implementation. Third, through a national survey of community college personnel, the book covers significant new territory in the discussion of work we need to do collaboratively as community colleges. Fourth, this book captures the unique and special mission of American community colleges. Our work is the work of social justice, and we carry this work out in society at a greater volume, with greater intentionality, and through greater expertise than any other sector of higher education. In this arena, community college should lead"--
A good kind of subversion -- Community colleges and upward mobility -- How big are the gaps? -- Adding academic capital to students' lives -- Funding higher education equitably -- Establishing best practices for on-campus student experiences -- Creating intuitive and supportive transitions -- Placing historically underserved students in selective universities -- Developing leaders who can affect institutional change -- Implementing the work of social justice in our colleges -- Social justice reform in the community college ecosystem -- Caution and courage.
Keywords: Social justice and education -- United States; Community colleges -- United States -- Aims and objectives; Educational equalization -- United States; EDUCATION / General